THE ROLE OF POLTEKIM SOCIALIZATION IN MOTIVATING STUDENTS OF SMAN 2 TANGERANG - Midah Purwanti; Kelvianto Ismail (Jurnal Abdimas Imigrasi, 2020)
This socialization activity carried out at SMAN 2 Tangerang is used as a means to add information to class XII students about one of the options for continuing education to a higher level, namely the immigration Polytechnic official college as an alternative to PTN or PTS, as well as to motivate students. in order to continue to be enthusiastic in undergoing education Broadly speaking, this socialization activity includes presentation activities regarding the introduction of the Immigration Polytechnic campus, registration requirements, registration procedures, study programs, tips, and sharing about life on the Immigration Polytechnic campus which is carried out to class XII students at SMAN 2 Tangerang, where they make preparations. In this activity, the presentation material was prepared by cadets of the Immigration Polytechnic who are running PPL and KKN in the Tangerang Kanim and have been simulated beforehand to fellow cadets and employees of the Tangerang Kanim. The benefits of this socialization activity are that students become enthusiastic and motivated to be able to join education at the Immigration Polytechnic. The benefits that are also felt by the cadets who carry out the socialization at SMAN 2 Tangerang are that the cadets can practice in making presentations and public speech. In addition, in this socialization, cadets also want to inform that state or private universities are not the only options available to continue higher education, the Immigration Polytechnic is one of the official universities that can be used as an alternative for students to continue to higher education. higher education level. Overall, this socialization activity is expected to provide motivation to students of SMAN 2 Tangerang to remain enthusiastic in implementing education and it is hoped that in the future they can join the Immigration Polytechnic knighthood.